Student Management for Children with Special Needs: Case Study of Blind Students at SLB-A PRPCN Palembang - Rohman, Asep; Khairunnisya, Khairunnisya; Randa, Gusti (LP. Ma'arif Janggan Magetan, 2023)
This research is entitled Student Management for Children with Special Needs: Case Study of Blind Students at SLB-A PRPCN Palembang. This research aims to understand the management of students with special needs who are blind in depth and discover strategic factors and problems. This research is a Collective Case Study which breaks down several scopes and finds strategic factors for student management. Data collection methods are interviews, observation and documentation, while data analysis techniques are carried out by data collection, data reduction, data presentation and data verification. Data validity techniques use source triangulation and technical triangulation. Based on the research results, 12 important factors were found in student management at SLB-A PRPCN Palembang, 3 of which were strategic factors, namely student acceptance, training and self-development and alumni tracking. First, student acceptance is carried out openly. The school prepares for the meeting, new students fill out forms and complete the requirements and take a self-assessment. Early assessment aims to obtain clear information regarding prospective students, both physical and mental readiness. Second, training and personal development are carried out effectively. The school carries out religious training such as recitations and tahfidz of the Koran as well as training in music, computers, massage and scouting. Third, the school implements the alumni tracer program well. A group of alumni who have established alumni ties. These three things are strategic factors in student management for children with special needs who are blind.